Macroprudential Policy Framework : A Practice Guide - Krishnamurti, Damodaran; Lee, Yejin Carol (Washington, DC: World Bank, 2014)
This practice guide is primarily intended as a reference and guidance for emerging market economies in their migration to a formal macroprudential policy framework. It relies largely on the existing wisdom, knowledge, and experience and was written with the intention of assisting policy makers (and the World Bank staff working with these authorities) in the implementation of macroprudential policy frameworks in jurisdictions with the following characteristics representative of a typical emerging market and developing economy: 1) a simple and bank-dominated financial system where other financial sector segments are much smaller, but growing; 2) banking supervision function is within the central bank; 3) financial sector regulation/supervision is not integrated; 4) uncertain availability of quality data. A macroprudential policy framework is not a silver bullet for safeguarding financial stability. It is also useful to highlight that a macroprudential policy framework cannot take the place of other public policy frameworks. While pursuing macroprudential policy to build a more resilient financial system, authorities should also take into consideration the significant financial development needs that may exist in their respective jurisdictions. This Practice Guide has been structured in a logical sequence that mirrors implementation. The second and third sections are laid out to clarify and provide some context to the concept of a macroprudential approach to supervision and discuss the institutional framework. The fourth and fifth sections deal with the operational aspects of macroprudential policy framework that are timely detection of systemic risks using early warning systems and addressing the buildup of systemic risks with macroprudential policy instruments.